ANALISIS PENGARUH BUDAYA ORGANISASI DAN KETERLIBATAN KERJA TERHADAP LOYALITAS ANGGOTA DALAM MENINGKATKAN KINERJA PADA SUAR INDONESIA DI KEDIRI - Sukatiningsih Sukatiningsih (Universitas Islam Kadiri, 2020)
This study discusses the influence of organizational culture , work engagement , and loyalty members in improving the performance of members . In particular the objectives of this study are : 1. To analyze the influence of organizational culture on the loyalty of members . 2. Analyze the effects of job involvement on loyalty members . 3. To analyze the effect on the performance of member loyalty . 4. Analyze the influence of organizational culture on kineja . 5. Analyze the effects of work engagement on performance. Respondents in this study were 29 members of the Indonesian Flares In Kediri , with saturated sampling technique . Technical analysis of the data used in this research is quantitative analysis with Path Analysis SPSS version 18 with the first regression measuring the influence of organizational culture and work engagement to loyalty members , and the second regression measures the influence of organizational culture and work involvement on performance. The results showed the influence of organizational culture on the loyalty of members of 63,84% , job involvement influence the loyalty of 50,84% , the effect on the performance of member loyalty of 82,81% , the influence of organizational culture on performance of 71,06 , job involvement influence on the performance of 63,68